Growth Kinetics and Extracellular Enzyme Secretion of Aureobasidium pullulans m11-2 as an Alternative Source of Polysaccharidases for Winemaking - Sevillano, María Eugenia (2025)
Microbial enzymes, due to their efficiency, specificity, and sustainability, are central to innovative biotechnological strategies aimed at optimizing industrial processes such as winemaking. In this study, the potential of Aureobasidium pullulans m11-2, a native dimorphic fungus from the wine ecosystem, was evaluated as a source of hydrolytic enzymes capable of degrading grape cell wall polysaccharides. The strain was identified at the molecular level and characterised in terms of its morphology. To maximise enzyme production, various culture media were tested. Among the concentrations tested, the optimal levels of glucose and pectin were 1 g L−1 and 10 g L−1, respectively. The partially constitutive and inducible nature of the various polysaccharidase activities (pectinases, cellulases, and xylanases) was confirmed. The effect of grape skins (a winemaking by-product) on microbial growth and enzyme synthesis was evaluated, achieving a pectinase activity of 0.622 U mL−1 when combined with 1 g L−1 of glucose. Maximum enzyme yields were detected during the exponential growth phase in both citrus pectin and grape skin media, suggesting favorable conditions for continuous bioprocessing. These results confirm that A. pullulans m11-2 is an interesting microbial option for producing polysaccharidases that can be adapted to sustainable production systems.